Hierarchical polymer coating for optimizing the antifouling and bactericidal efficacies. Issue 14 (21st September 2016) - Yan, Shunjie; Song, Lingjie; Li, Zhihong; Luan, Shifang; Shi, Hengchong; Xin, Zhirong; Li, Shenghai; Yang, Yuming; Yin, Jinghua
Abstract: The bacteria-repellent and bactericidal functionalities in a single system are generally need to be carefully optimized in order to obtain the highest antibacterial performance. In this study, the controlled SI-PIMP strategy was developed for creating hierarchical polymer brushes possessing the bacteria-repellent and bactericidal functionalities. To obtain a bactericidal surface with minimal interference to its nonfouling property, optimization studies were conducted by facilely tailoring the surface density of the quaternary ammonium compound moieties through control over the monomer concentration. An optimal hierarchical polymer coating showed potent protein and bacteria repellence as well as certain bactericidal property. The longlasting antibacterial performance was also achieved due to the good balance between the dual functionalities. The tenability of the hierarchical polymer coating is applicable to surface chemistries for biosensors, molecular imaging, and biomedical applications. Graphical abstract: